Bacterial microbiome and physicochemical properties of irrigation water and soil in Chonto type tomato from Boyaca, Colombia - Forero-Pineda, Nicolas; Correa-Castro, Tania-Alejandra; Serrano-Cely, Pablo-Antonio; Forero-Ulloa, Fabio-Emilio; Cely-Reyes, Germán-Eduardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Tomato cultivation ranks fourth in vegetable production in Boyaca. The largest production of Chonto tomato in greenhouses is supplied by the Alto Chicamocha irrigation and drainage district since it is the main agricultural production unit for the department. To investigate the physicochemical conditions of the soil and irrigation water in the crop and bacterial communities associated with the greenhouse Chonto tomato crop, a total of 15 crops of 50×50 m located within the irrigation and drainage district of Alto Chicamocha were analyzed. Soil and irrigation water samples were analyzed and the bacteriome associated with the crop rhizosphere was characterized. From the physicochemical results obtained, we observed a significant relationship between crop attributes, the physicochemical properties of soil, and irrigation water in the different study zones. On the other hand, in the bacterial composition associated with the crop (soil and irrigation water), a relationship was found between the genera Sphingomonas spp. and Sphingobium spp. with crop quality for the different crops evaluated.